PRE AND POST-MOULT PRODUCTIVE EFFICIENCY IN FOUR VARIETIES OF INDIGENOUS ASEEL CHICKEN DURING DIFFERENT PRODUCTION CYCLES - Z. Ahmad; A. W. Sahota; M. Akram; A. Khalique; A. S. Jatoi; M. Shafique; M. Usman; U. Khan (Journal of Animal and Plant Sciences, 2014)
The objective of current study was to assess the effect of moulting on productive efficiency in Aseel chickens at different phases of age. A total of 168 hens, 42 from each of four varieties (Mushki, Lakha, Mianwali and Peshawari) divided into 3 age groups, young (50-67 weeks), medium (80 -97 weeks) and old (115-132 weeks) were maintained in cages during pre and post-moult phases. The data thus collected during both the phases were subjected to analysis of variance in Randomized Complete Block Design. The results showed that overall productive   efficiency remained better in post-moult as compared to pre-moult phase. Mushki showed significantly higher egg production, egg mass, egg weight, and better FCR/ dozen eggs. Feed intake was higher in Peshawari variety while, body weight and FCR/Kg egg mass showed non-significant differences. The birds of younger age showed significantly higher feed intake, egg mass, egg production, and better FCR/dozen eggs, while, egg weight and FCR/kg egg mass were not affected by age. Older birds showed significantly higher body weight.
Keywords: Aseel Chicken; Production performance; Pre-moult; Post-moult; Variety